The Influence of Income Diversification, Operational Efficiency, Credit Risk, and Bank Size on the Profitability of the Banking Subsector Listed on the Indonesia Stock Exchange Period 2019-2023 - Giawa, Berkat; Purba, Sahala; Simanjuntak, Wesly Andri; Simanjuntak, Arthur (Future Science, 2025)
This study investigates the influence of specific banking characteristics on profitability within the Indonesian banking sector. The research examines whether income diversification, operational efficiency, credit risk, and bank size significantly impact profitability measures among financial institutions listed on the Indonesia Stock Exchange. The investigation focuses on determining whether these four key banking variables demonstrate meaningful associations with profitability performance. From a population of 47 banking institutions, 10 representative companies were selected through purposive sampling methods. Financial data was obtained from annual reports of banking subsector companies covering the period 2019-2023. The study employs a quantitative descriptive framework utilizing multiple analytical approaches including descriptive statistics, classical assumption testing, and hypothesis assessment through regression analysis using SPSS version 26 software. The findings reveal that: Income diversification exhibits a positive but statistically insignificant relationship with profitability measures; Operational efficiency shows a negative and statistically significant effect on profitability indicators; Credit risk demonstrates a negative and statistically significant influence on profitability performance; and Bank size displays a positive but statistically insignificant impact on profitability outcomes. For future research endeavors, this study suggests extending the observation period, enhancing methodological transparency, and complementing financial statement analysis with comprehensive multi-source data integration.